Nivolumab plus Brentuximab vedotin +/- bendamustine combination therapy: a safe and effective treatment in pediatric recurrent and refractory classical Hodgkin lymphoma - Greve, Patrick; Beishuizen, Auke; Hagleitner, Melanie; Loeffen, Jan; Veening, Margreet; Boes, Marianne; Peperzak, Victor; Diez, Claudius; Meyer-Wentrup, Friederike (Frontiers in Immunology, 2023)
Classical Hodgkin lymphoma (cHL) is the most common pediatric lymphoma. Approximately 10% of patients develop refractory or recurrent disease. These patients are treated with intensive chemotherapy followed by consolidation with radiotherapy or high-dose chemotherapy and autologous stem cell reinfusion. Although this treatment is effective, it comes at the cost of severe long-term adverse events, such as reduced fertility and an increased risk of secondary cancers. Recently, promising results of inducing remission with the immune checkpoint inhibitor nivolumab (targeting PD-1) and the anti-CD30 antibody-drug conjugate Brentuximab vedotin (BV) +/- bendamustine were published. Here we describe a cohort of 10 relapsed and refractory pediatric cHL patients treated with nivolumab + BV +/- bendamustine to induce remission prior to consolidation with standard treatment. All patients achieved complete remission prior to consolidation treatment and are in ongoing complete remission with a median follow-up of 25 months (range: 12 to 42 months) after end-of-treatment. Only one adverse event of CTCAE grade 3 or higher due to nivolumab + BV was identified. Based on these results we conclude that immunotherapy with nivolumab + BV +/- bendamustine is an effective and safe treatment to induce remission in pediatric R/R cHL patients prior to standard consolidation treatment. We propose to evaluate this treatment further to study putative long-term toxicity and the possibility to reduce the intensity of consolidation treatment.